Annotated Systematic Checklist of the Aphids (Hemiptera: Aphidomorpha) of Turkey - Kök Şahi̇n; Özdemi̇r Işil (Zootaxa, 2021)
This comprehensive checklist of aphids presents a total of 591 species, including 26 subspecies, from 147 genera belonging to 15 subfamilies in three families distributed over three superfamilies of Aphidomorpha recorded from 1903 to 2020 in Turkey. In the current list, the systematic positions with the genus and species names of some taxa have been revised, and some species have been downgraded to subspecies in accordance with recent changes in nomenclature. Seven species have been removed from the Turkish fauna and four species that were not included in the previous checklist have been added to the list. Also, 59 of the listed species (about 10% of Aphidomorpha) are evaluated as alien to the Turkish fauna, and the distribution of all species in Turkey is given.